2018
DOI: 10.5812/jcrps.80331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Usability of a Nationwide Pharmacy Information System in Iran: Application of Nielson’s Heuristics

Abstract: Background: This study was conducted to evaluate Pharmacy Information Systems (PIS), which are widely used in Iranian hospitals to identify the usability problems of PIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…In two studies, the identified problems in this principle had the highest average severity. 21,38 Other studies have shown that the identified problems in this principle are among the major problems, 25,37 which are consistent with the results of the present study. The principle of error prevention is based on the fact that the design of the system should be such that it eliminates error-prone conditions.…”
Section: Feature Articlesupporting
confidence: 93%
See 3 more Smart Citations
“…In two studies, the identified problems in this principle had the highest average severity. 21,38 Other studies have shown that the identified problems in this principle are among the major problems, 25,37 which are consistent with the results of the present study. The principle of error prevention is based on the fact that the design of the system should be such that it eliminates error-prone conditions.…”
Section: Feature Articlesupporting
confidence: 93%
“…Also, most of the identified problems in this principle were related to effectiveness and satisfaction. This principle, also in two studies, 22,25 showed the highest frequency of problems. The results of these studies are consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Given the difference in computer experience and expertise of users and the unfamiliarity of information systems developers with the user population, the design of these systems is not often tailored to the needs and interests of their users. Also, according to previous studies [ 6 9 ], poor design of information systems leads to users' fatigue, and dissatisfaction, as well as, system inefficiency and rejection. The good design of an information system contributes to its usability.…”
Section: Introductionmentioning
confidence: 99%